Application of Green Architecture Principles in the Design of Public Buildings in Tropical Urban Areas - Mulyana; Ar.Marson Maizi (PT Mattawang Mediatama Solution, 2025)
AbstractRapid urbanization in tropical cities increases energy use and environmental degradation, highlighting the need for green architecture to promote sustainable and resilient public buildings. This study investigates the application of green architecture principles in the design of public buildings in tropical urban areas, emphasizing their impact on environmental sustainability. Using a quantitative explanatory approach and multiple regression analysis with EViews 12, the research examines the influence of three primary variables green design principles, tropical climate adaptation, and building energy efficiency on environmental sustainability (Y). Data were collected from 120 respondents, including architects, facility managers, and users of public buildings across Indonesia’s tropical cities. The results show that all three variables have a positive and significant effect on environmental sustainability, with energy efficiency demonstrating the strongest influence (β₃ = 0.356, p < 0.001). The model’s explanatory power (R² = 0.731) indicates that 73.1% of sustainability performance is explained by the independent variables, confirming that design, adaptation, and energy management must operate synergistically. The findings highlight that integrating passive design strategies, efficient energy systems, and adaptive technologies reduces energy consumption while improving user comfort and environmental resilience. Moreover, the study emphasizes policy implications, suggesting the need for building codes, financial incentives, and professional training programs that encourage sustainable design in public infrastructure. It concludes that the implementation of green architectural principles in tropical urban contexts provides a tangible pathway toward achieving sustainable cities and communities (SDG 11), promoting both environmental preservation and socio-economic well-being. Keywords: Energy Efficiency, Green Architecture, Public Buildings, Sustainable Design, Tropical Climate Adaptation